Language Style Analysis of Female Characters in Horror Movie “Presence” - Winarsih; Sugiharti, Dona Rahayu (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2025)
Abstract. Language style is how people have choices and alternatives in the way they use the language. Language is part of verbal communication. This research explores the concept of language style, focusing specifically on how it is utilized by female characters in the horror film “Presence.” The primary aim of this study is to describe the types of language styles employed by the female characters and to determine which style is most dominantly used throughout the movie. The study adopts a descriptive qualitative research method, where data are obtained through a close analysis of selected utterances from the movie script. These utterances are then categorized according to the five language styles proposed by Martin Joos: frozen, formal, consultative, casual, and intimate. From the analysis, a total of 23 utterances spoken by female characters were identified as relevant data. These were distributed among three language style categories: one utterance was classified as consultative, fourteen as casual, and eight as intimate. The findings show that casual language style is the most frequently used. This dominance is attributed to the contextual and thematic elements of the film. “Presence” centers around themes of power, rumor, and empathy, and is set within a suburban household—an environment that naturally invites informal, emotionally expressive, and conversational interactions. The use of casual and intimate styles reflects the close relationships and tense dynamics among the characters, which align with the movie’s psychological and mysterious atmosphere. Thus, the study demonstrates how language style in cinematic dialogue is influenced by both narrative content and setting. Keywords/Kata Kunci: female characters, horror movie, language style, sociolinguistics, utterances